IMPACT OF IMPELLER EROSION ON THE ENERGY EFFICIENCY OF PUMP SYSTEMS - Ernazarov Alisher Qoryogdiyevich; Turgunov Bohodirjon Khamdamjon ogli (Journal Park Publishing, 2025)
In this study, the decline in energy efficiency caused by impeller erosion in centrifugal pumps, along with the resulting increase in hydraulic losses and changes in pump performance characteristics, was investigated. The findings show that non-uniform wear of impeller blades, surface degradation due to cavitation, and geometric alterations caused by interaction with fine abrasive particles lead to significant deviations in blade geometry. Even minor changes in the blade profile were found to affect flow direction, velocity distribution, and pressure fields, ultimately resulting in a decrease in pump efficiency. During the research, erosion patterns observed under real operating conditions were measured and evaluated, and the resulting flow losses were compared using hydraulic theory and experimentally obtained performance curves. Results indicate that erosion of 1–2 mm at the blade tips increases swirl intensity in the flow, raises energy consumption, and reduces the pump’s head-generating capability. Furthermore, cavitation-induced surface damage was shown to increase localized flow resistance, causing the pump’s operating point to shift away from the nominal regime. The conducted analyses demonstrate that timely detection of impeller wear is crucial for maintaining pump efficiency. The findings have practical significance for scheduling maintenance intervals, selecting materials for pumps operating in abrasive environments, and improving algorithms for digital monitoring systems designed to assess impeller health.
Keywords: Impeller wear, pump efficiency, hydraulic losses, useful work coefficient, flow channel geometry, pressure head, cavitation wear, abrasive particle effect, local drag coefficient, energy efficiency, eddies, wear, stability.